2020
DOI: 10.14336/ad.2019.1229
|View full text |Cite
|
Sign up to set email alerts
|

Age-related CCL12 Aggravates Intracerebral Hemorrhage-induced Brain Injury via Recruitment of Macrophages and T Lymphocytes

Abstract: Circulating factors associated with aging have been shown to be involved in the development of age-related chronic and acute brain diseases. Here, we aimed to investigate the roles and mechanisms of CCL12, a circulating factor that is highly expressed in the plasma of aged rodents after intracerebral hemorrhage (ICH) using parabiosis and ICH models. Neurological deficit score (NDS), mortality rate, brain water content (BWC), and levels of inflammatory factors were determined to assess the degree of ICH-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…In addition, Yang et al reported that mCCL12 produced by injured alveolar epithelial cells could promote pulmonary fibrosis in mice by recruiting profibrotic macrophages through CCR2 in mice (102). The increased peripheral level of mCCL12 in old mice can aggravate brain injury induced by intracerebral hemorrhage by recruiting macrophages and T cells (103). In the tumor microenvironment, mCCL12 has been reported to play an essential role in tumor progression by regulating the recruitment and polarization of macrophages.…”
Section: Ccl12 In Liver Diseasementioning
confidence: 99%
“…In addition, Yang et al reported that mCCL12 produced by injured alveolar epithelial cells could promote pulmonary fibrosis in mice by recruiting profibrotic macrophages through CCR2 in mice (102). The increased peripheral level of mCCL12 in old mice can aggravate brain injury induced by intracerebral hemorrhage by recruiting macrophages and T cells (103). In the tumor microenvironment, mCCL12 has been reported to play an essential role in tumor progression by regulating the recruitment and polarization of macrophages.…”
Section: Ccl12 In Liver Diseasementioning
confidence: 99%
“…Besides IL-1, CCL5, and CCL12, other immune modulatory proteins were also reduced in Fpr1 −/− mice after ICH. The reduction of these factors may alleviate brain inflammation and promote neurorepair (36)(37)(38). The elevated blood mitochondria-derived N-formyl peptides could also activate circulating FPR1 + immune cells such as neutrophils and monocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The needle was kept in position for an additional 5-min period and then slowly removed to prevent backflow. Exogenous IL-18 (20 μg/kg) was purchased from R&D systems (9139-IL-050/CF; RRID:AB-2895090), and it was injected 1 hr before inducing ICH according to previous description (Huang et al, 2020;Wu et al, 2020;Yang et al, 2018). The purity of recombinant mouse IL-18 was more than 90% by SDS-PAGE visualized with silver staining and quantitative densitometry by Coomassie® blue staining according to the manufacturer.…”
Section: Establishment Of the Experimental Ich Model In Micementioning
confidence: 99%